Using Square Wave Input for Wireless Power Transfer - Kazuya Yamaguchi; Takuya Hirata; Ichijo Hodaka (International Journal of Electrical and Computer Engineering (IJECE), 2016)
A wireless power transfer (WPT) circuit is composed of a transmitting circuit with an AC power supply and a receiving circuit with a load, and the circuits are wirelessly connected each other. Then a designer chooses the wave form of the AC power supply. Many papers about WPT adopt a sinusoidal wave as the input. The frequency of the sinusoidal wave is generally determined to the resonant frequency of the circuit for high power transfer. Since the number of circuit elements in the power supply to generate a square wave is much less than that of a sinusoidal wave, WPT with a square wave input should be treated. In fact, some papers about WPT adopt a square wave as the input, and adjust the frequency of the square wave to the resonant frequency of the circuit. In this paper, we examine how the frequency of a square wave input affects power and efficiency of WPT circuits, and propose a procedure how to determine the frequency of the input to improve power and efficiency. Finally we discuss which wave should be adopted as an input and how the frequency of the input should be determined, regardless of whether resonant phenomena occur or not.